Using coupled fish behavior–hydrodynamic model to investigate spawning migration of Japanese anchovy, Engraulis japonicus , from the East China Sea to Taiwan - CHEN‐YI TU; YU‐HENG TSENG; TAI‐SHENG CHIU; MAO‐LIN SHEN; CHIH‐HAO HSIEH (Fisheries Oceanography, 2012)
Adult Japanese anchovies ( Engraulis japonicus ) migrate from the East China Sea to the coastal region of Taiwan to spawn around late winter and early spring and, later, their larvae constitute important fisheries in Taiwan. However, their migration route and its mechanism remain unclear. To investigate their spawning migration, we used a coupled fish behavior–hydrodynamic modeling approach. The physical field is simulated by the Pacific Ocean adaptation of the TaIwan Multi‐scale Community Ocean Model (TIMCOM) and the fish migration by Lagrangian tracer tracking with the aid of approximation of fish swimming behavior. We investigated three fish behavioral scenarios: (i) passive tracking of the current, (ii) swimming along with the current, and (iii) swimming along with the current and then changing to swimming toward the optimal spawning temperature. The comparison with and without Changjiang discharge is used to investigate the impacts of discharge reduction due to the Three Gorges Dam. Our results suggest that spawning migration of Japanese anchovy from the East China Sea to Taiwan may be aided by the China Coastal Current and that adult anchovies cannot reach the spawning site by passive advection alone. Thus, the swimming behavior of anchovies is crucial during the spawning migration, as it provides extra velocity and the orientation to the favorable spawning grounds. In addition, the adult anchovy is unlikely to reach the coastal area of Taiwan without Changjiang discharge. Our findings indicate that a coupled fish behavior–hydrodynamic model can help understand the influences of physical environment on the migration of Japanese anchovies.